1987
DOI: 10.1104/pp.83.4.945
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations in Pulvini from Samanea saman

Abstract: Biological Sciences Group U-42, University ofConnecticut, Storrs, Connecticut 06268 ABSTRACI The movement of Samwaea leaflets depends upon changes in the curvature of the pulvinus at the base of each leaflet. Pulvinar bending and straightening, in turn, are driven by the movement of water between opposing (extensor and flexor) sides of the pulvinus. Although water movement depends on water potential (1) and thus on osmotic potential (X) and hydrostatic pressure (P), none of these parameters have been measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…We conducted additional pH experiments at various times during 51 h of DD in the medium containing 0.4 M mannitol (osmotic potential = -1.2 MPa). This value is similar to the most negative water potential reported for Samanea motor tissue (7).…”
Section: Abstracitsupporting
confidence: 87%
“…We conducted additional pH experiments at various times during 51 h of DD in the medium containing 0.4 M mannitol (osmotic potential = -1.2 MPa). This value is similar to the most negative water potential reported for Samanea motor tissue (7).…”
Section: Abstracitsupporting
confidence: 87%
“…Mannitol lowered the water potential of the solution, and this, in turn, would lower cell turgor. Gorton (1987a) reported that flexor cell turgor changes in vivo during leaflet movement, and we propose that these alterations in turgor may regulate H+ pump activity in vivo, as depicted in Fig. 1.…”
Section: Effects Of the Clock On H+ Transportmentioning
confidence: 64%
“…The following discussion is based on (a) Figures 3 and 4; (b) I values measured by the droplet method (from Gorton [2]) as compared to the Chardakov method (Fig. 1); (c) measured ir values (from Gorton [2]); and (d) differences between the two derived P values, Pdr and PCh (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Merrill3 are often chosen for experimental work because they are large and easily dissected, so it is possible to do in vitro work on the antagonistic extensor and flexor sides ofthe pulvinus separately. Such experiments suggest that ion uptake in swelling pulvinar cells may be driven by an outwardly directed H+-pump (3,4) and that the magnitude and direction of H' fluxes depends on the I4 of the bathing medium (6 4Abbreviations: i = water potential (i = ir + P); wr = osmotic potential; P = hydrostatic pressure; *id, = water potential measured on extensor and flexor sides of intact pulvini using the droplet method (from Gorton [2]); ich, = water potential measured on excised strips ofextensor and flexor tissues using the Chardakov procedure; P& = pressure calculated using idr and r; Pch = pressure calculated using *Ch and r; PceII = pressure attributable to the water status and resistance to expansion of individual cells; Ptissue = pressure imposed on a given cell by other cells. When extensor or flexor tissues were excised from open or closed pulvini, they elongated immediately (Fig.…”
mentioning
confidence: 99%